PENINGKATAN PENGETAHUAN KOSAKATA DASAR BAHASA SUNDA MELALUI MODEL INDUKTIF KATA BERGAMBAR - Sopy Subhaniati Gustini; Dingding Haerudin Haerudin (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2023)
The purpose of this study was to determine the effect of the pictorial word inductive model on increasing knowledge of basic Sundanese vocabulary in class VII-F students of SMP Negeri 1 Pangandaran in the 2022/2023 academic year. The research method used was a quasi experiment with the one-group pretest and posttest research design. The subjects in this study were 32 students of class VII-F. Before being given the treatment the average pretest score was 39.9 and the posttest score was 84.06. The calculation results obtained that there is a significant difference between the pretest average and posttest average with tcount > ttable, namely 25.63 > 2.45. Based on the results of the analysis that has been obtained, the average number of students' pretest and posttest results in percentage, namely from 39.97% increased to 84.06%. So using the pictorial word inductive model can increase knowledge of the basic Sundanese vocabulary in 2023 by 44.09%.